Optimized planning for intraoperative planar permanent‐seed implant - Fung, Albert Y. C. (J Appl Clin Med Phys, 2002)
We describe a fast, PC‐based optimization planning system for a planar permanent‐seed implant. Sites where this system is applicable include brain, lung, and head and neck. The system described here allowsplacing ribbons of different strengths and of different lengths along and across the implant plane. The program takes full advantage of the availability of different source strengths in inventory, and attempts to find configurations of ribbons that result in optimal dose uniformity over the prescription plane. Dosimetry is based on the AAPM TG 43 Report [R. Nath et al., Med. Phys. 22, 209–234 (1995)]. Compared with TG 43 parameters, the classical tables underestimate the I‐125 source strengths needed by 40%. The use of several source strengths improves the plan. Typical optimization yields dose uniformity of 10%, and computing times are within 2–3 min No further enhancement is obtained if ribbons are placed in a grid pattern as opposed to the (simpler) arrangement along parallel lines. Nor is it valuable to have variable ribbon lengths. For an I‐125 implant the optimization system described here is a practical alternative to the (strictly speaking inapplicable) classical systems. It calculates correctly the total source strengths, and ‐ most notably ‐ generates plans with optimal dose uniformity. The fast computing time is well suited for planning during surgery in the operating room. PACS number(s): 87.53Jw, 87.53.Tf